Acquisition of Customary Rights of Customary Communities In Customary Lands for Corporate Business Use Rights - Pratama, Arya Putra Rizal; Wulandari, Sinar Aju (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
Indonesia has regulations on land management related to the economy based on the public interest. The use of land by a corporation is carried out by granting cultivation rights (HGU) over the ground through a Government stipulation. However, with increasing investment activity, land has become essential to support capital inflows in Indonesia. With the shift in land requirements for investment, customary land has become an attraction for investors in business activities in the agricultural, fishery or plantation sectors. This research is legal research (doctrinal analysis) using a conceptual approach (conceptual approach) and statutory approaches (statute approach). The results of this study explain that the use of land in corporations located on customary land through HGU is a legal action and can be carried out as long as it does not interfere with or eliminate the essence of the characteristics of the customary land rights. Then, granting HGU over customary land can be done in consultation with the customary community with corporations through the government. However, the deficiency in granting HGU over customary land when this period expires threatens the loss of the status of customary land and customary rights.